Synthesis and Cytotoxic Activity of Conjugates of Mitochondrial-Directed Cationic Compound F16 with Ursane-Structure Triterpenic Acids Containing a Polyhydroxylated A-ring - Anna Spivak; Darya Nedopekina; Eldar Davletshin (Chemistry Proceedings)
We chemically linked corosolic and asiatic acids and a synthetic polyoxygenated analogue of ursolic acid via an alkyl linker to the cationic mitochondrial targeting compound F16 (4-(1H-indole-3-ylvinyl)-N-methylpyridinium iodide). The conjugates were tested for cytotoxic activity against two human lung adenocarcinoma cell lines, H1299 and A549, and non-cancerous mouse embryonic fibroblast cells. The results showed that conjugation of polyoxygenated triterpene acids with the terminal cationic fragment F16 in the C-28 side chain enhanced cytotoxicity (30–35 fold) compared to the original natural ursolic acid. However, the presence of hydroxyl or acetyl functions in the A-ring of F16 conjugates of corosolic or asiatic acids resulted in a significant decrease in cytotoxicity compared to their structural analogue, the F16 derivative of ursolic acid.